Pengaruh Penggunaan Pupuk Organik Cair Nira Aren (Arenga pinnata) Terhadap pertumbuhan Tanaman Bawang Merah (Allium ascalonicum) - Siti Soburatul Jannah; Maya Ekaningtias; Nurmiati (Otus Edu Journal Prodi Tadris IPA Biologi UIN Mataram, 2023)
The need for red onions has not yet been balanced by the amount of production, so the government always brings in red onions through imports to meet the community's needs. The aim of this research was to determine the effect of the growth of shallots (Allium ascalonicum) on the application of liquid organic fertilizer from sap (Arenga pinnata). The approach used in this research is quantitative research. The research was carried out using a completely randomized design (CRD) with different concentrations of liquid organic fertilizer from palm sap, with concentrations of 0 ml, 20 ml, 40 ml, 60 ml, 80 ml and 100 ml, a total of 6 treatments, with 5 replications. The results of the research show that based on the ANOVA test, the calculated F value was 1,954, while the F table (0.05) on the diameter of shallot plant bulbs shows that there is a significant influence provided that F calculated>F table. Apart from that, based on the results of the anova test, the parameters of plant height (0.178), the significant value of the number of plant leaves (0.067), and the significant value of the diameter of the plant tuber (0.133) so that the research results obtained indicate that liquid organic fertilizer of sugar palm sap has an effect on height growth. plants, number of leaves, and diameter of shallot bulbs (Allium ascalonicum).